2017
DOI: 10.1002/jsfa.8791
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pomological characteristics and flavour components of fruits and virgin olive oil following wastewater irrigation and soil tillage

Abstract: Agronomic practices may affect considerably the commercial and nutritional values and the sensorial quality of the commodities. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 50 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…Despite the contribution of the higher net photosynthetic rate of FI, RDI, and SDI plants to higher productivity, the increase in crop yield, relative to SDIAF, was correlated with the seasonal water volume, in line with previous studies . Meanwhile, the higher crop yield of FI trees in relation to DIS treatments was associated with the higher weight of the fruits.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Despite the contribution of the higher net photosynthetic rate of FI, RDI, and SDI plants to higher productivity, the increase in crop yield, relative to SDIAF, was correlated with the seasonal water volume, in line with previous studies . Meanwhile, the higher crop yield of FI trees in relation to DIS treatments was associated with the higher weight of the fruits.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the decrease in water supply increased the stressful conditions experienced by the plants, as observed by the physiological performance of the trees and, consequently, the necessity for them to invest in the secondary metabolism to protect against oxidative stress . In fact, several studies reported that stressful conditions increase the accumulation of phenolic compounds in olive fruit . Although the increased accumulation of phenolic compounds improves their antioxidant properties, oils are occasionally characterized as excessively bitter .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations